Management of Anterior Crossbite Using an Elastomeric Functional Apparatus (Orthoplus): A Case Report - Harika Ixzarina; Arlette Setiawan (Journal of Social Research, 2026)
Anterior crossbite is one of the most common malocclusions encountered during the mixed dentition period and may negatively affect dental function, craniofacial development, and esthetics if left untreated. Early interceptive orthodontic intervention is therefore recommended to prevent the progression of more complex malocclusions. This case report aims to describe the management of anterior crossbite using a prefabricated elastomeric myofunctional appliance (Orthoplus EFT Slim) in a pediatric patient. The method involved clinical examination, radiographic evaluation, diagnosis of a Class I skeletal relationship with dentoalveolar anterior crossbite, and interceptive treatment using a removable elastomeric functional appliance. The patient was instructed to use the appliance daily in conjunction with myofunctional exercises to improve tongue posture, lip competence, and breathing patterns. Treatment progress was evaluated monthly over a three-month period. The results showed that correction of the anterior crossbite was achieved within the first month, as indicated by the transition from negative to positive overjet. Subsequent evaluations demonstrated stable occlusal relationships, improved anterior interdigitation, and enhanced orofacial muscle function, including improved nasal breathing and lip seal. No relapse or complications were observed throughout the treatment period. In conclusion, the use of a prefabricated elastomeric myofunctional appliance is effective for correcting anterior crossbite during the mixed dentition stage, providing both dental correction and functional improvement. Early intervention supports stable treatment outcomes and may help prevent the future development of more severe malocclusions; however, long-term follow-up is recommended to further validate these findings.